2022
DOI: 10.3390/plants11040513
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated TiO2 Nanocomposite Delays the Postharvest Ripening Phenomenon through Ethylene Metabolism and Related Physiological Changes in Capsicum Fruit

Abstract: Capsicum is one of the most perishable fruit which undergo rapid loss of commercial value during postharvest storage. In this experiment our aim is to evaluate the effect of photoactivated TiO2 nano-particle complexed with chitosan or TiO2-nanocomposite (TiO2-NC) on extension self-life of Capsicum fruit and its effect on related morphological, physiological and molecular attributes at room temperature (25 °C). Initially, TiO2-NC coated fruits recorded superior maintenance of total soluble solids accumulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Mansourbahmani et al [ 18 ] observed that the TPC data after 35 days of treatment by applying 20% potassium permanganate mixed with zeolite in a 1:2 ratio were 35% higher than for untreated tomatoes. Ghosh et al [ 45 ], in 2022, applied photoactivated titanium dioxide and chitosan to create a film for coating ‘Tejaswani’ peppers stored at room temperature (25 °C). The treated peppers exhibited maintained soluble solid content (SSC) along with enhanced color.…”
Section: Resultsmentioning
confidence: 99%
“…Mansourbahmani et al [ 18 ] observed that the TPC data after 35 days of treatment by applying 20% potassium permanganate mixed with zeolite in a 1:2 ratio were 35% higher than for untreated tomatoes. Ghosh et al [ 45 ], in 2022, applied photoactivated titanium dioxide and chitosan to create a film for coating ‘Tejaswani’ peppers stored at room temperature (25 °C). The treated peppers exhibited maintained soluble solid content (SSC) along with enhanced color.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that titanium oxide nanoparticles (TiO 2 ) prolong the shelf life of fruits has also been shown in numerous studies. Studies conducted by Yong and Liu [ 39 ], Jiang et al [ 40 ], Fathi et al [ 41 ], Ghosh et al [ 42 ], and Patel and Mishra [ 43 ] are a few of these studies. Antimicrobial agents can be added to food packaging materials to suppress bacteria and extend the product's realistic useable life.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic peaks at 1015 cm −1 and 720 cm −1 corresponded to the -C-H of the PET. Compared to the PET, the characteristic peak at 2899 cm −1 in the NC-TiO2/PET was the typical band for the cellulose nanomaterial molecules, and the strong characteristic peaks below 700 cm −1 were due to the bending of the -Ti-O bonds in the NC-TiO2/PET [21]. In addition, the characteristic peaks of the cellulose nanofibers were clearly visible in the broad bands' 3600-3000 cm −1 region and were caused by telescopic vibrations within and between the O-H bonds.…”
Section: Chemical Characterizationsmentioning
confidence: 96%